2019
DOI: 10.1021/acs.jafc.9b05618
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Effects in Vitro and in Vivo of Novel Angiotensin-Converting Enzyme Inhibitory Peptides from Bovine Bone Gelatin Hydrolysate

Abstract: In this study, we investigated the antihypertensive effects in vitro and in vivo of novel angiotensin-converting enzyme inhibitory (ACEI) peptides purified and identified from bovine bone gelatin hydrolysate (BGH). Thirteen ACEI peptides were identified from BGH, and among which, RGL-(Hyp)-GL and RGM-(Hyp)-GF exhibited high ACE inhibition with IC50 values of 1.44 and 10.23 μM. Molecular docking predicted that RGM-(Hyp)-GF and ACE residues of Glu384, His513, and Lys511 formed hydrogen-bonding interactions at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“…Notably, in vivo the QIGLF reached its maximum effect faster than RVPSL, implying that QIGLF might be absorbed faster than RVPSL. And previous study has shown that the SBP maximum lowering of LSGYGP, β‐casein LHLPLP, CMP and RGM was occurred at 3, 4, 4 and 6 h after administration, respectively (Quiros et al ., 2007; Miguel et al ., 2007b; Zhao et al ., 2019; Cao et al ., 2020). The appearance may be due to the different absorption and metabolism, or the different transport rates at the location of the operation (Li et al ., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in vivo the QIGLF reached its maximum effect faster than RVPSL, implying that QIGLF might be absorbed faster than RVPSL. And previous study has shown that the SBP maximum lowering of LSGYGP, β‐casein LHLPLP, CMP and RGM was occurred at 3, 4, 4 and 6 h after administration, respectively (Quiros et al ., 2007; Miguel et al ., 2007b; Zhao et al ., 2019; Cao et al ., 2020). The appearance may be due to the different absorption and metabolism, or the different transport rates at the location of the operation (Li et al ., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The anti‐hypertensive effects of QIGLF and RVPSL were evaluated by measuring the changes of SBP and DBP in the SHRs using the tail–cuff method after administration (Cao et al ., 2020). Before the measurement, SHRs were preheated in an insulation bucket at 37‐39°C for 5 min to undertake that the rat’s tail artery pulsations were measurable.…”
Section: Methodsmentioning
confidence: 99%
“…Depression and hypertension are important medical impairments that are extensively investigated with collagen hydrolysate [ 41 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 ]. Recently, a couple of efforts by the same group were presented on diminution of hypertension using novel collagen hydrolysate [ 41 , 149 ].…”
Section: Diseasementioning
confidence: 99%
“…Angiotensin I-converting enzyme (ACE), a zinc protease, plays a crucial role in regulating blood pressure for its ability of converting angiotensin I to the potent vasoconstrictor angiotensin II in the renin-angiotensin system and the deactivation of the vasodilator bradykinin in the kallikrein-kinin system (Cao et al, 2020;Ko et al, 2012). The application of ACE inhibitors has been accepted as one of the major therapeutic approaches to reducing hypertension (Wijesekara & Kim, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the detection and identification of ACE inhibitors from foods has attracted increasing attention for safety concerns (Admassu et al, 2018;Ko et al, 2012). Anti-hypertensive peptides with strong ACE inhibitory activity have been reported to be derived from animals (Kocak et al, 2020), fruits (Memarpoor-Yazdi et al, 2020), vegetables (Patten et al, 2016), eumycetes (Amorim et al, 2019) and other marine sources (Pujiastuti et al, 2019). Besides, there have been various studies conducted on their activities (García-Mora et al, 2017;Majumder & Wu, 2015;Raji et al, 2020).…”
Section: Introductionmentioning
confidence: 99%